Characterization of Anopheles minimus CYP6AA3 expressed in a recombinant baculovirus system - Soamrutai Boonsuepsakul (2018)
Metabolism by cytochrome P450 monooxygenases is a major mechanism implicated in resistance of insects to insecticides, including pyrethroids. We previously isolated the cytochrome P450 CYP6AA3 from deltamethrin-selected resistant strain of Anopheles minimus mosquito, a major malaria vector in Thailand. In the present study, we further investigated the role of CYP6AA3 enzyme in deltamethrin metabolism in vitro. The CYP6AA3 was expressed in Spodoptero frugiperda (Sf9) insect cells via baculovirus-mediated expression system. The enzymatic activity of CYP6AA3 in deltamethrin metabolism was characterized after being reconstituted with An. minimus NADPH-cytochrome P450 reductase and a NADPH-regenerating system. The contribution of CYP6AA3 responsible for deltamethrin metabolism was determined by measurement of deltamethrin disappearance following the incubation period and deltamethrin-derived compounds were detected using combined gas chromatography mass spectrometry analysis. 3-Phenoxybenzaldehyde was a major product of CYP6AA3-mediated deltamethrin metabolism. Deltamethrin degradation and formation of metabolites were NADPH-dependent and inhibited by piperonyl butoxide. Deltamethrin was catalyzed by CYP6AA3 with an apparent Km of 80.0 ± 2.0 and Vmax of 60.2 ± 3.6 pmol/min/pmol P450. Furthermore, deltamethrin cytotoxicity assays by 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and trypan blue dye exclusion were examined in Sf9 insect cells, with and without expression of CYP6AA3. Results revealed that CYP6AA3 could play a role in detoxifying deltamethrin in the cells. Thus, the results of this study support the role of CYP6AA3 in deltamethrin metabolism. © 2008 Wiley-Liss, Inc.